2016
DOI: 10.3168/jds.2015-10083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extending the interval from Presynch to initiation of Ovsynch in a Presynch-Ovsynch protocol on fertility of timed artificial insemination services in lactating dairy cows

Abstract: The specific objective of this study was to determine if increasing the interval between the Presynch and Ovsynch portion of the Presynch-Ovsynch protocol (Presynch: PGF2α-14 d-PGF2α and Ovsynch: GnRH-7 d-PGF2α-56 h-GnRH-16-20 h-timed artificial insemination) from 12 to 14 d would reduce the fertility of lactating dairy cows not detected in estrus after Presynch that receive timed artificial insemination (TAI). Cows from 4 commercial dairy farms (n=3,165) were blocked by parity (primiparous vs. multiparous) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…These programs can help reduce time to pregnancy after the end of the voluntary waiting period through rapid insemination of most cows after Presynch and immediate submission to TAI of those cows not detected in estrus. Programs such as Presynch-Ovsynch (Chebel et al, 2006;Fricke et al, 2014;Giordano et al, 2016) and Presynch-Cosynch (Stevenson, 2011;Ribeiro et al, 2012) have been extensively evaluated and are widely used for first service management of lactating dairy cows (Caraviello et al, 2006;Ferguson and Skidmore, 2013). In spite of the fact that these programs may effectively improve reproductive performance of dairy heifers, they have not been evaluated extensively in research and are rarely used for heifers in commercial farms (NAHMS, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These programs can help reduce time to pregnancy after the end of the voluntary waiting period through rapid insemination of most cows after Presynch and immediate submission to TAI of those cows not detected in estrus. Programs such as Presynch-Ovsynch (Chebel et al, 2006;Fricke et al, 2014;Giordano et al, 2016) and Presynch-Cosynch (Stevenson, 2011;Ribeiro et al, 2012) have been extensively evaluated and are widely used for first service management of lactating dairy cows (Caraviello et al, 2006;Ferguson and Skidmore, 2013). In spite of the fact that these programs may effectively improve reproductive performance of dairy heifers, they have not been evaluated extensively in research and are rarely used for heifers in commercial farms (NAHMS, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since a presynchronization strategy was used in the study, the ovulation in response to GnRH of the Ovsynch protocol could be higher, as reported by other authors that obtained over 80% of ovulation rate to the first GnRH of the FTAI protocol in Presynch-Ovsynch or Double-Ovsynch-synchronized cows (Gumen et al, 2012;Ayres et al, 2013). However, the ovulation rate of the present study was similar to other studies that reported rates around 60-70% (Souza et al, 2008;Giordano et al, 2013;Giordano et al, 2016). It should be mentioned that the 16.8 µg dose of buserelin acetate used on D0 of our study represents 68% more in relation to the recommended dose of 10.0 µg (Monteiro et al, 2015).…”
Section: Ovarian Dynamics and Estrus Expressionsupporting
confidence: 87%
“…The proportion of cows with CL on D6, which was the moment of first PGF of the FTAI protocols, was high (~90%) and did not differ (P = 0.34) between experimental groups (Table 3). Studies using Presynch-Ovsynch or Double-Ovsynch also reported high (87 to 100%) proportion of cows with CL on that day (Ayres et al, 2013;Carvalho et al, 2015;Dirandeh et al, 2015;Giordano et al, 2016). Therefore, in our study, more than 90% of the cows had at least one CL during development of the preovulatory follicle, providing an adequate circulating P4 milieu for optimized fertility.…”
Section: Ovarian Dynamics and Estrus Expressionsupporting
confidence: 48%
See 2 more Smart Citations